Manfaat dan Tujuan Mendongeng untuk Pendidikan Anak Usia Dini: Benefits and Objectives of Storytelling for Early Childhood Education - Shofwan, Arif Muzayin Shofwan (JURNAL TILA ( Tarbiyah Islamiyah Lil Athfaal ), 2022)
Storytelling activities are usually carried out by a teacher to early childhood students. There are many benefits of storytelling activities for early childhood students. Therefore, storytelling activities must continue to be developed in early childhood education. This descriptive qualitative research with literature study will discuss the various benefits and objectives of storytelling for early childhood. The data analysis technique uses content analysis by sorting out data according to the objectives and benefits of the research. This study found the following points. First, storytelling is an activity to tell fictitious stories that don't really happen to instill the best values ??from the story and take lessons from the worst values ??from the story. Second, the purpose of storytelling for early childhood is to form good behavior and instill character values ??in children so that they have balance and cognitive, affective, and psychomotor development. Third, the benefits of storytelling for early childhood include: training concentration, sharpening memory sharpness, developing language skills, fostering interest in reading, improving critical thinking skills, and bringing closer emotional relationships between teachers and students.